Are we Truly "Safer-At-Home"? A Test of Contextual Effects on Mental Health and Drug Overdose Incidents During the COVID-19 Pandemic. (July 2022) - Konkel, Rebecca Headley; Harris, Michelle N.; Hoffman, Chrystina Y.
This study examined whether the social restrictions stemming from COVID-19 impacted the locations of mental health and drug overdose incidents, while controlling for immediate and community contextual indices. Addresses for mental health/overdose calls to law enforcement or emergency medical services between January 1, 2018 and August 13, 2020 were collected from one police department in the Midwestern United States. Businesses and previous victimization/offending were joined with parcels (level-1; N = 20, 019), whereas local services and socioeconomic indicators were joined with block groups (level-2; N = 32), to allow for a multi-level (HLM7) examination of context on mental health/overdose incidents. Event Rate Ratios (ERR) revealed the greatest contextual effects took place following social distancing mandates. Findings highlight the importance of allocating to areas with the highest likelihood of reporting incidents and suggest that parcels with a history of sex offenses, drug offenses, and prior mental health calls may benefit the greatest from preventative resources.